(untitled) (Journal of Computational Mathematics, 2021)
If f^(i))(α)(α=a, i=0,1,...,k-2) are given, then we get a class of the Hermite approximation operator Qf=F satisfying F^(i)(α)=f^(i)(α), where F is the many-knot spline function whose knots are at points y_i:=y_0